2022
DOI: 10.3390/architecture2010010
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Impact of Sensitive Sub-Categories of Demographic Variables on Safety Climate of High-Rise Building Projects

Abstract: The identification of significant areas impacting safety performance has always been a key concern for construction management researchers. This paper aims to examine the diversified influence of sensitive sub-categories of demographic variables on construction safety climate (SC). The data relating to fourteen demographic variables and twenty-four formerly validated SC statements were collected from forty-one under-construction high-rise buildings in Pakistan. The variances in respondents’ distribution among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Previous studies concluded that political (PR), social safety (SR), and legal risks (LR) are often more serious and sensitive in mega construction projects [9][10][11][12][13]. Unfortunately, previous researchers have paid little consideration to exploring the effects of PRs in the international construction industry or international joint ventures (IJVs) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies concluded that political (PR), social safety (SR), and legal risks (LR) are often more serious and sensitive in mega construction projects [9][10][11][12][13]. Unfortunately, previous researchers have paid little consideration to exploring the effects of PRs in the international construction industry or international joint ventures (IJVs) [10].…”
Section: Introductionmentioning
confidence: 99%